Peran Guru Bimbingan Konseling dalam Merealisasikan Sistem Pendidikan Anti Narkoba di Kalangan Remaja: Studi Kasus Prodi Bimbingan Konseling Unimed - Faiq, Muhammad Fadhal; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Panjaitan, Geovany; Syahfitri, Intan Dwita; Tambunan, Novelyn A.C.M; Br Kaban, Priska; Sari, Siti Rahma (IAI Nasional Laa Roiba Bogor, 2024)
Drugs are substances or drugs that are natural, synthetic, or semi-synthetic in nature that cause hallucinations and stimulation. Meanwhile, according to the Narcotics Law article 1 paragraph 1 states that narcotics are artificial substances or those derived from plants that have the effect of hallucinations, decreased awareness, and cause addiction. The method used in this research is a qualitative approach. The data collection techniques used are observation, interviews, and documentation with the number of respondents studied in this study were 10 respondents. This study aims to determine how much the role of counseling teachers in preventing and handling cases of drug abuse in adolescents and the impact of drug abuse on the lives of adolescents as a whole.